2015
DOI: 10.5539/res.v7n3p184
|View full text |Cite
|
Sign up to set email alerts
|

Religious Tolerance in Malaysia: A Comparative Study between the Different Religious Groups

Abstract: This paper reports a study conducted on 2400 respondents in Malaysia on their tolerance and mutual respect to each other religion. The study is important in order to map the religious tolerance in Malaysia and the findings can be used to plan future action by related authorities. The respondents, males and females of different ethnics, from the age 18 to 45 years old were obtained randomly from all over the country. The respondents were given booklets of questionnaire containing statements provided with respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Phinney and Nakayama in (Onyekwuluje, 1998) suggested that children's view on race and ethnic is influenced mostly by the family. Meanwhile, a study on multicultural found that behavior among SD (elementary school) students in Jakarta represents the values they adopt from the socialization agents such as mother, religious teacher, and friends [9]. behavior.…”
Section: Designmentioning
confidence: 99%
“…Phinney and Nakayama in (Onyekwuluje, 1998) suggested that children's view on race and ethnic is influenced mostly by the family. Meanwhile, a study on multicultural found that behavior among SD (elementary school) students in Jakarta represents the values they adopt from the socialization agents such as mother, religious teacher, and friends [9]. behavior.…”
Section: Designmentioning
confidence: 99%
“…The concept of mutual understanding seems vital as people should not interrupt the practices of other religious adherents (Kasmo, Usman, Taha, Salleh, & Alias, 2015). Every individual or religious adherents should respect the doctrines of other religions.…”
Section: Understandingmentioning
confidence: 99%
“…From this point, I tolerance is a way of managing conflicts in a diverse society. Not everyone can accept religious, ethnic, cultural, or moral differences (Kasmo, Hamdi, Taha, Salleh, & Alias, 2015). Hence, conflicts or crises in life occur when there is coercion.…”
Section: Introduction: What Is Tolerance?mentioning
confidence: 99%